Changing energy use futures : second international conference on energy use management, held 22-26 October 1979, Los Angeles, California, vol. I - Fazzolare, Rocco; Smith, Craig B. (New York: Pergamon Press, 1979)
This conference has been planned to examine the issues, problems, and perspectives of energy utilization. It focuses on the progression and evolution of society faced with resource limitations; and ways of minimizing undesirable socio-economic impacts.
Includes bibliographical references and index.
ne 24/04/2018
Loans
Keywords: Energy conservation; Power resources; Human ecology; Power resources--Management; Energy policy